Impact of a Generated Magnetic Field at the Schumann Resonance Frequency on Skin Blood Perfusion and Peripheral Pulse Amplitudes - Mayrovitz, Harvey N (Curēus (Palo Alto, CA), 2025)
A pilot study was conducted in six young adult male volunteers (25.8±1.3 years) to determine if there was evidence of an effect of a locally applied magnetic field at the Schumann Resonance fundamental frequency of 7.8 Hz. The field was generated by magnets attached to the shaft of an electronically controlled motor and applied for 20 minutes to the wrist region near the radial and ulnar arteries. The alternating magnetic field was activated after the subject had been supine and resting for 20 minutes. Skin blood perfusion (SBF) was measured on the thenar eminence via laser Doppler flux (LDF), and finger pulses were measured by photoplethysmography (PPG) on the index finger as indicators of localized hemodynamics and heart rate variability (HRV) determined as a measure of possible central effects. These measurements were done before magnet activation and after its deactivation, so each subject served as their own control. No separate sham procedure was used. Results showed that LDF decreased by 23.6±22.5% (p<0.05) and PPG pulse amplitude decreased by 35.5±18.7% (p<0.05) from pre- to post-magnetic field exposure based on a non-parametric Wilcoxon signed-rank test. There was no statistically significant change in HRV, although this study did not evaluate the possibility of a different systemic effect. These pilot findings are based on a minimal number of subjects but provide new data and lay the groundwork for a more extensive investigation of this process, which seems warranted based on the present findings.